2018
DOI: 10.1108/ijppm-12-2017-0325
|View full text |Cite
|
Sign up to set email alerts
|

Cost of quality measurement in food manufacturing companies: the Greek case

Abstract: Purpose The purpose of this paper is to focus on the cost of quality (CoQ) of food manufacturing companies. The study aims at empirically validating the conceptual structure of the core dimensions of CoQ (prevention, appraisal, internal and external failure cost) and determining their level and relationships. Determining the reasons for not measuring the CoQ as well as the barriers-difficulties and benefits of the CoQ measurement is also an aim of the present study. Design/methodology/approach Greek food man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 56 publications
2
45
0
1
Order By: Relevance
“…Using novel approaches to gather quality cost data (Karg et al, 2011); identifying how a company makes use of the quality cost information (Cheah et al, 2011;Pires et al, 2017); determining how quality cost data can be used (Al-Tmeemy et al, 2012); providing organization-wide CoQ information (Ozkan and Karaibrahimoglu, 2013); studying how to encourage managers to use quality cost information (Novas and Saraiva, 2014); getting detailed service quality and cost data (Johnston and Ozment, 2015); developing suitable approaches and methods to reduce the burden of CoQ data collection (Rabfeld et al, 2015); considering CoQ data collection methods (Zhang et al, 2015); examining the practical implications of the different uses of qualityrelated cost information (Pires et al, 2017), the reasons why managers use the quality-related cost information according to a diagnostic profile or an interactive profile (Pires et al, 2017) and CoQ data collection in several departments (Czajkowski, 2017); generating new knowledge on the implementation of CoQ measurement (Moschidis et al, 2018); collecting subjective CoQ data from more than one company representative as well as objective data from the company files (Psomas et al, 2018); conducting interviews instead of questionnaires for CoQ data collection (Glogovac and Filipovic, 2018) (continued )…”
Section: Coq Data and Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using novel approaches to gather quality cost data (Karg et al, 2011); identifying how a company makes use of the quality cost information (Cheah et al, 2011;Pires et al, 2017); determining how quality cost data can be used (Al-Tmeemy et al, 2012); providing organization-wide CoQ information (Ozkan and Karaibrahimoglu, 2013); studying how to encourage managers to use quality cost information (Novas and Saraiva, 2014); getting detailed service quality and cost data (Johnston and Ozment, 2015); developing suitable approaches and methods to reduce the burden of CoQ data collection (Rabfeld et al, 2015); considering CoQ data collection methods (Zhang et al, 2015); examining the practical implications of the different uses of qualityrelated cost information (Pires et al, 2017), the reasons why managers use the quality-related cost information according to a diagnostic profile or an interactive profile (Pires et al, 2017) and CoQ data collection in several departments (Czajkowski, 2017); generating new knowledge on the implementation of CoQ measurement (Moschidis et al, 2018); collecting subjective CoQ data from more than one company representative as well as objective data from the company files (Psomas et al, 2018); conducting interviews instead of questionnaires for CoQ data collection (Glogovac and Filipovic, 2018) (continued )…”
Section: Coq Data and Informationmentioning
confidence: 99%
“…In this era of increased globalization of markets and liberalization of local economies, the interest of researchers and practitioners in the CoQ concept is increasing, as evidenced by the large number of publications in different contexts and disciplines (Uyar and Neyis, 2015;Grbac et al, 2015;Johnston and Ozment, 2015;Sawan et al, 2018;Psomas et al, 2018). Since the introduction of the concept of CoQ in the 1950s, substantial work has been done by numerous researchers and practitioners in a variety of areas such as manufacturing, construction, building and highway engineering (Sharma et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to Bayram and Ünğan (2020), prevention costs of quality resembles organizational efforts to improve processes before problems occur, and therefore can enhance organizational learning capabilities by turning learning opportunities into actions that foster organizational performance. In fact, the work of Psomas et al (2018) also suggested that organization that decided to invest in prevention costs of quality can be more competitive in the market due to reduced accidents and wasted resources. Moreover, Ayach et al (2019) believed that investments in prevention and appraisal activities lower the total quality cost.…”
Section: This Is Whatmentioning
confidence: 99%
“…Business organizations face competitive and complex circumstances because of the rapid growth of technology and the changing socio-economic environment (Psomas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The existing models of quality costs, on the category of internal failures, do not describe the effects that defective items have on cost. Additionally, the same models do not identify decisions and actions that companies should do after a defective item is identified, which influences the determination of the related effects and, consequently, the failure cost (Alglawe et al , 2019; Arabian et al , 2013; Campanella, 1999; Chopra and Garg, 2011, 2012; Duarte et al , 2016; Fons, 2012; Holota et al , 2016; Jaju et al , 2009; Johnson, 1995; Juran and Godfrey, 1999; Kiani et al , 2009; Lim et al , 2015; Malik et al , 2016; Omar and Murgan, 2014; Ozcan, 2012; Pires et al , 2013; Plewa et al , 2016; Psomas et al , 2018; Sailaja et al , 2015; Schiffauerova and Thomson, 2006, 2013; Su et al , 2009; Superville and Gupta, 2001).…”
Section: Introductionmentioning
confidence: 99%